A lightweight fire-retardant cement-based composite wallboard and a method for preparing the same
Patent Information
- Application Number
- CN202611102920.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]该技术方案中,原材料生石灰的占比高达15%~23%,其水化生成氢氧化钙过程中伴随显著的体积膨胀,极易导致墙板内部产生微裂纹,木质纤维虽能改善抗裂性,但木质素易吸水吸潮,导致板材耐水性差、软化系数低,在潮湿环境中易腐烂降解,造成孔隙率增加、强度下降,并成为霉菌滋生温床
本申请通过引入多羧基丙烯酸酯作为统一界面改性介质,采用分步预混工艺分别将阻燃剂A与硅烷化复合纤维、阻燃剂B进行预先分散包覆,在不增加阻燃填料总用量的条件下,同步提升了墙板的阻燃性能与力学强度。同时,通过对聚磷酸铵的硅烷预处理以及基材表面的硅烷界面处理,进一步提升了阻燃组分的长效稳定性与UV涂层的附着持久性,使成品墙板兼具轻质高强、多级协同阻燃的综合性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of lightweight building materials technology, and more specifically, to a lightweight flame-retardant cement-based composite wall panel and its preparation method. Background Technology
[0002] Lightweight composite wall panels, with their advantages of being lightweight yet strong, providing thermal insulation, modular construction, and energy efficiency, have become the mainstream building material for prefabricated building envelopes, and replacing traditional solid concrete walls is an inevitable trend in the industry. Currently, research on lightweight cement-based composite wall panels focuses on optimizing the properties of the substrate itself, such as mechanical properties, thermal insulation, and high-temperature fire resistance. Mainstream research systems cover categories such as foamed concrete wall panels, fiber-reinforced cement-based wall panels, and basalt fiber modified composite wall panels. However, traditional single-substrate materials often face challenges such as difficulty in balancing strength and lightweight, limitations in fire resistance due to organic fillers, or the brittleness of inorganic materials.
[0003] Patent application CN104692722A discloses a lightweight composite wall panel, including a substrate with fireproof boards laminated to the upper and lower surfaces of the substrate; the substrate is composed of the following components by mass percentage: 5%~10% clay particles, 18%~25% cement, 15%~23% quicklime, 5%~10% wood fiber, 2%~5% binder, 28%~35% quartz powder, 4%~7% aluminum hydroxide, and 3%~5% recycled substrate material.
[0004] In this technical solution, the proportion of quicklime as a raw material is as high as 15% to 23%. During its hydration to form calcium hydroxide, it is accompanied by significant volume expansion, which can easily lead to micro-cracks inside the wall panel. Although wood fiber can improve crack resistance, lignin is prone to absorbing water and moisture, resulting in poor water resistance and low softening coefficient of the board. In a humid environment, it is easy to rot and degrade, causing increased porosity, decreased strength, and becoming a breeding ground for mold. Summary of the Invention
[0005] In order to overcome the shortcomings of the existing technology, this application provides a lightweight flame-retardant cement-based composite wall panel and its preparation method.
[0006] This application provides a lightweight, flame-retardant cement-based composite wall panel, comprising a substrate and a UV-cured coating laminated on the surface of the substrate, wherein the substrate is made of the following raw materials in parts by weight: The ingredients are: 70-80 parts cement, 20-30 parts auxiliary cementitious materials, 4-10 parts silanized composite fiber, 1-3 parts flame retardant A, 6-12 parts flame retardant B, 6-15 parts polycarboxylated acrylate, 10-18 parts lightweight porous aggregate, 3-5 parts water-based environmentally friendly adhesive, 0.5-2 parts nano silica, 1-3 parts hydroxypropyl methylcellulose, and 32-39 parts water.
[0007] In this scheme, a high-dosage cement-based composite auxiliary cementitious material is used. Cement hydration provides early strength, while the auxiliary cementitious material consumes calcium hydroxide through a pozzolanic reaction, synergistically forming a dense matrix and providing stable basic mechanical strength. Polycarboxylated acrylates are used as a general interface modifier; the carboxyl groups have a tendency to chemically adsorb onto inorganic surfaces, improving the interfacial bonding between components such as silanized composite fibers and lightweight porous aggregates and the cement matrix, thus enhancing the mechanical properties of the wall panel. Flame retardants A and B work synergistically to form an expanding carbon layer and inorganic barrier when heated, exerting a multi-temperature zone synergistic flame retardant effect. Lightweight porous aggregates achieve lightweighting and insulation through internal pores; nano-silica fills micropores and promotes secondary hydration; hydroxypropyl methylcellulose improves the water retention and prevents segregation of the slurry; and water-based environmentally friendly adhesive ensures the overall bonding integrity of the green body in the early stages of molding.
[0008] Preferably, the auxiliary cementing material is selected from any one of slag powder, fly ash, and silica fume.
[0009] Further optimizations include using silica fume for high-strength applications, fly ash for low-cost general-purpose applications, and slag powder for high-toughness applications.
[0010] Preferably, the lightweight porous aggregate is selected from any one of expanded perlite, vitrified microspheres, and ceramsite.
[0011] Further optimizations include: expanded perlite for ultra-lightweight thermal insulation applications, vitrified microspheres for general applications, and lightweight ceramsite for high-load applications.
[0012] Preferably, the flame retardant A comprises silanized ammonium polyphosphate, pentaerythritol, and dicyandiamide.
[0013] Preferably, the method for preparing the silanized ammonium polyphosphate includes the following steps: The silane coupling agent pre-hydrolyzed solution and ammonium polyphosphate were added to the reactor and mixed at 25-30℃ for 3-4 hours. After solid-liquid separation, washing, drying, and heat treatment, silanized ammonium polyphosphate was obtained.
[0014] In this solution, ammonium polyphosphate is impregnated with a silane coupling agent pre-hydrolyzed solution to form a silane molecular film on the surface of the ammonium polyphosphate, which reduces its continuous leaching during long-term service in the cement matrix, delays the consumption of the flame-retardant active ingredients, and improves flame-retardant durability.
[0015] Preferably, the flame retardant B comprises aluminum hydroxide and zinc borate.
[0016] In this scheme, aluminum hydroxide decomposes at around 200℃, absorbs heat to cool down, and releases water vapor to dilute the combustible gas. Zinc borate forms a glassy boron oxide protective layer at a higher temperature to promote char formation. The two, together with intumescent flame retardant A, form a multi-temperature zone synergistic flame retardant effect.
[0017] Preferably, the polycarboxylated acrylate is added in the form of a polycarboxylated acrylate emulsion, and its preparation method includes the following steps: Under an inert atmosphere, 42-48 parts of butyl acrylate, 2-5 parts of acrylic acid, 1-3 parts of methacrylic acid, 0.5-2 parts of itaconic acid, 1-3 parts of N-hydroxymethylacrylamide, and 12-20 parts of polyethylene glycol methyl ether methacrylate are mixed evenly and added to an aqueous phase containing emulsifier. After pre-emulsification, the temperature is raised to 70-80℃, an initiator is added, and the reaction is carried out for 4-6 hours. After neutralization, an acrylate emulsion is obtained.
[0018] In this scheme, the carboxyl functional groups provided by acrylic acid, methacrylic acid and itaconic acid in the emulsion can form coordination bonds with calcium ions in cement hydration products and form hydrogen bonds with hydroxyl groups on the surface of fiber and other components, thereby strengthening the inorganic-organic interface bond; N-hydroxymethylacrylamide forms a dense polymer network through film self-crosslinking, and polyethylene glycol methyl ether methacrylate imparts flexibility to the film layer. The two work together to buffer stress, suppress microcracks and reduce matrix brittleness.
[0019] Preferably, the emulsifier comprises sodium dodecyl sulfate and OP-10.
[0020] Preferably, the method for preparing the silanized composite fiber includes the following steps: After mixing alkali-free glass fiber and acidified polypropylene fiber, the mixture is impregnated in a pre-hydrolyzed solution of silane coupling agent, mixed at 25~30℃ for 5~7h, followed by solid-liquid separation, washing, drying, and heat treatment to obtain silanized composite fiber.
[0021] In this scheme, after treatment with silane coupling agent, an active organic coating layer is formed on the fiber surface, which enhances the interfacial bonding force between the fiber and the cement hydration matrix.
[0022] Preferably, the preparation method of the acidified polypropylene fiber is as follows: add polypropylene fiber to dilute sulfuric acid, mix at 60~70℃ for 30~60 min, separate solid and liquid, wash, dry, and set aside.
[0023] Preferably, the method for preparing the pre-hydrolyzed solution of the silane coupling agent includes the following steps: Mix the silane coupling agent and the ethanol aqueous solution evenly, adjust the pH to 3.5~5.5, and mix for 40~60 minutes to obtain the pre-hydrolyzed solution.
[0024] Preferably, the silane coupling agent is silane KH-550 or silane KH-560.
[0025] Preferably, the volume ratio of the silane coupling agent to the aqueous ethanol solution is (3~5):(95~97).
[0026] Preferably, the substrate is pre-coated with a methacryloyloxypropyltrimethoxysilane prehydrolysate before the UV-cured coating is applied.
[0027] Preferably, the preparation method of the methacryloyloxypropyltrimethoxysilane prehydrolysate includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly, the pH was adjusted to 4.0-5.0, and the mixture was stirred for 30-60 minutes to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0028] Preferably, the volume ratio of the methacryloyloxypropyltrimethoxysilane to the aqueous ethanol solution is (3~5):(95~97).
[0029] In this scheme, after the hydrolysate is applied to the surface of the cement substrate, the silanol groups can undergo a dehydration condensation reaction with the hydroxyl groups on the cement surface to form stable covalent bonds and complete the inorganic end anchoring. When water-based UV coatings are subsequently applied, a chemically bonded transition layer is built between the inorganic cement substrate and the organic UV coating to achieve a strong connection between the two phases.
[0030] Preferably, the UV-cured coating uses a commercially available water-based UV-curable coating.
[0031] Preferably, the substrate further includes 5 to 10 parts by weight of pretreated phosphogypsum.
[0032] Preferably, the method for preparing the pretreated phosphogypsum includes the following steps: The raw phosphogypsum ore was mixed with lime at a mass ratio of 100:(3~5), ball-milled for 45~60 minutes, aged, dried, and ground to obtain pretreated phosphogypsum.
[0033] In this scheme, lime is used to neutralize the acidic and harmful impurities in phosphogypsum, eliminating the interference of acidic components on the normal hydration of cement. The sulfate ions provided by calcium sulfate in phosphogypsum under alkaline conditions can activate the hydration activity of auxiliary cementitious materials, promote the formation of ettringite, fill the pores of the matrix, and further improve the density and mechanical properties.
[0034] This application also provides a method for preparing a lightweight flame-retardant cement-based composite wall panel, comprising the following steps: S1: Mix a portion of polycarboxylated acrylate and flame retardant A evenly, add silanized composite fiber and mix evenly to obtain mixture A; S2: Mix the remaining polycarboxylated acrylate and flame retardant B evenly to obtain mixture B; S3: Mix cement, auxiliary cementitious materials, nano silica, hydroxypropyl methylcellulose, and optional pretreated phosphogypsum evenly, add water and water-based environmentally friendly adhesive and mix evenly, add mixture A, mixture B and lightweight porous aggregate and mix evenly, pour into mold, vent, allow to stand for pre-curing, demold, and after standard curing, obtain the substrate; S4: After coating the substrate surface with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution, the coating is rolled, cured, and post-treated to obtain a lightweight flame-retardant cement-based composite wall panel.
[0035] In this scheme, a portion of the emulsion is first mixed and dispersed with flame retardant A and silanized composite fibers to ensure uniform distribution of functional components within the emulsion medium. During subsequent molding, film formation in the emulsion achieves interfacial bonding and in-situ fixation of the flame retardant components. The remaining emulsion is then premixed with flame retardant B to form a uniform flame-retardant slurry. The gelling powder and functional powder are pre-dry-mixed uniformly before adding water to ensure uniform dispersion of nano-silica and cellulose ethers within the gelling system, better leveraging their microstructure optimization and water retention control effects. Subsequently, the premixed components are incorporated and uniformly mixed with lightweight porous aggregates to guarantee uniform distribution of all components and stable performance after molding. A silane transition layer is coated onto the substrate surface, followed by roller coating with UV paint for curing, strengthening the interfacial bond between the inorganic substrate and the organic coating, and improving coating adhesion and durability.
[0036] In summary, this application has the following beneficial effects: This application introduces polycarboxylated acrylate as a unified interface modification medium and employs a stepwise premixing process to pre-disperse and coat flame retardant A with silanized composite fibers and flame retardant B, thereby simultaneously improving the flame retardant performance and mechanical strength of the wall panel without increasing the total amount of flame retardant filler. Furthermore, through silane pretreatment of ammonium polyphosphate and silane interface treatment of the substrate surface, the long-term stability of the flame retardant components and the adhesion and durability of the UV coating are further enhanced, resulting in a finished wall panel that combines lightweight, high strength, and multi-stage synergistic flame retardancy. Detailed Implementation
[0037] The present application will be further described in detail below with reference to the embodiments.
[0038] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0039] The alkali-free glass fiber has a length of 6~12mm, a single filament diameter of 10~15μm, a moisture content of ≤0.1%, and a tensile strength of ≥2500MPa; The length of chopped polypropylene fibers is 8~15mm, and the diameter of the monofilament is 15~20μm; Nano-silica is a hydrophilic fumed nano-silica with an average particle size of 20-40 nm and a specific surface area of 150-300 m². 2 / g, purity ≥99.0%; Slag powder, fly ash, and silica fume are all made of Grade I special-grade powder for construction; slag powder is Grade S95 with an activity index ≥95%; fly ash is Grade I with a fineness ≤12%; silica fume has a purity ≥92% and a specific surface area ≥18000 m². 2 / kg, all three powders were free of lumps and impurities, and the volcanic ash exhibited excellent activity; Expanded perlite particle size 20~50 mesh; vitrified microspheres particle size 30~60 mesh; lightweight ceramic particles particle size 3~5 mm.
[0040] Preparation Examples 1-2: Silane Coupling Agent Pre-hydrolyzed Solution Preparation Example 1 The preparation method of the silane coupling agent pre-hydrolyzed solution in this preparation example includes the following steps: The silane KH-560 and ethanol aqueous solution with a volume ratio of 3:97 were mixed evenly, and the pH of the system was adjusted to 3.5 with a 10% acetic acid solution. The mixture was stirred at 300 r / min for 40 min at 25 °C to obtain the silane coupling agent pre-hydrolyzed solution.
[0041] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0042] Preparation Example 2 The preparation method of the silane coupling agent pre-hydrolyzed solution in this preparation example includes the following steps: The silane KH-550 and ethanol aqueous solution with a volume ratio of 5:95 were mixed evenly, and the pH of the system was adjusted to 5.5 with a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain the silane coupling agent pre-hydrolyzed solution.
[0043] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0044] Preparation Examples 3-5: Polycarboxylated acrylate emulsions Preparation Example 3 The preparation method of the polycarboxylated acrylate emulsion in this example includes the following steps: (a) Under a nitrogen atmosphere, 810 g of butyl acrylate, 72 g of acrylic acid, 36 g of methacrylic acid, 18 g of itaconic acid, 36 g of N-hydroxymethylacrylamide, and 288 g of polyethylene glycol methyl ether methacrylate were mixed evenly to obtain an oil phase. (b) Under a nitrogen atmosphere, 1260g of deionized water was added to the reactor, and stirring was started at 300r / min. 4.8g of sodium dodecyl sulfate and 3.0g of OP-10 were added slowly in sequence and stirred until homogeneous. The oil phase was then slowly added and pre-emulsified at 1000r / min for 40min to form a stable pre-emulsion. The temperature was then raised to 74℃, and ammonium persulfate aqueous solution was added in 5 portions. The total reaction time was 5h. After the reaction was completed, the mixture was cooled to room temperature, and the pH of the system was adjusted to approximately 7.0 with 5% ammonia. The mixture was filtered and diluted with deionized water to a solid content of approximately 45% to obtain a polycarboxylated acrylate emulsion.
[0045] The ammonium persulfate aqueous solution was prepared by mixing 7.6g of ammonium persulfate and 50mL of deionized water. In this experiment, the ammonium persulfate aqueous solution was added intermittently in five batches at volume ratios of 30%, 30%, 20%, 10%, and 10%, with each addition 15 minutes apart. The addition time was within 3 hours before the reaction.
[0046] Preparation Example 4 The preparation method of the polycarboxylated acrylate emulsion in this example includes the following steps: (a) Under a nitrogen atmosphere, 672 g of butyl acrylate, 70 g of acrylic acid, 42 g of methacrylic acid, 28 g of itaconic acid, 42 g of N-hydroxymethylacrylamide, and 252 g of polyethylene glycol methyl ether methacrylate were mixed evenly to obtain an oil phase. (b) Under a nitrogen atmosphere, 1070g of deionized water was added to the reactor, and stirring was started at 300r / min. 4g of sodium dodecyl sulfate and 3.2g of OP-10 were added slowly in sequence and stirred until homogeneous. The oil phase was then slowly added and pre-emulsified at 1000r / min for 40min to form a stable pre-emulsion. The temperature was then raised to 80℃, and ammonium persulfate aqueous solution was added in 5 portions. The total reaction time was 4h. After the reaction was completed, the mixture was cooled to room temperature, and the pH of the system was adjusted to approximately 7.0 with 5% ammonia. The mixture was filtered and diluted with deionized water to a solid content of approximately 45% to obtain a polycarboxylated acrylate emulsion.
[0047] The ammonium persulfate aqueous solution was prepared by mixing 6.6g of ammonium persulfate and 50mL of deionized water. In this experiment, the ammonium persulfate aqueous solution was added intermittently in five batches at a volume ratio of 30%, 30%, 20%, 10%, and 10%, with each addition 15 minutes apart. The addition time was within 2 hours before the reaction.
[0048] Preparation Example 5 The preparation method of the polycarboxylated acrylate emulsion in this example includes the following steps: (a) Under a nitrogen atmosphere, 840g of butyl acrylate, 40g of acrylic acid, 20g of methacrylic acid, 10g of itaconic acid, 20g of N-hydroxymethylacrylamide, and 260g of polyethylene glycol methyl ether methacrylate were mixed evenly to obtain an oil phase. (b) Under a nitrogen atmosphere, 1200g of deionized water was added to the reactor, and stirring was started at 300r / min. Sodium dodecyl sulfate 4.0g and OP-10 2.4g were added slowly in sequence and stirred until homogeneous. The oil phase was then slowly added and pre-emulsified at 1000r / min for 40min to form a stable pre-emulsion. The temperature was then raised to 70℃, and ammonium persulfate aqueous solution was added in 5 portions. The total reaction time was 6h. After the reaction was completed, the mixture was cooled to room temperature, and the pH of the system was adjusted to approximately 7.0 with 5% ammonia. The mixture was filtered and diluted with deionized water to a solid content of approximately 45% to obtain a polycarboxylated acrylate emulsion.
[0049] The ammonium persulfate aqueous solution was prepared by mixing 7.1g of ammonium persulfate and 50mL of deionized water. In this experiment, the ammonium persulfate aqueous solution was added intermittently in five batches at a volume ratio of 30%, 30%, 20%, 10%, and 10%, with each addition 15 minutes apart. The addition time was within 3 hours before the reaction.
[0050] Preparation Examples 6-7: Silanized Composite Fibers Preparation Example 6 The preparation method of the silanized composite fiber in this example includes the following steps: After mixing alkali-free glass fiber and acidified polypropylene fiber at a mass ratio of 6:4, the mixture was impregnated in the silane coupling agent pre-hydrolysis solution from Preparation Example 1, with a solid-liquid ratio of 1g:3mL. The mixture was stirred at 500r / min for 5h at 30℃, filtered, washed three times with deionized water, dried at 45℃ for 4h, and heat-treated at 80℃ for 25min to obtain silanized composite fiber.
[0051] The specific preparation method of acidified polypropylene fiber is as follows: the polypropylene fiber is immersed in dilute sulfuric acid with a mass fraction of 7% at a solid-liquid ratio of 1g:6mL, stirred at 300r / min for 30min at 60℃, filtered, washed three times with deionized water, and dried at 45℃ to constant weight for later use.
[0052] Preparation Example 7 The preparation method of the silanized composite fiber in this example includes the following steps: After mixing alkali-free glass fiber and acidified polypropylene fiber at a mass ratio of 7:3, the mixture was impregnated in the silane coupling agent pre-hydrolysis solution from Preparation Example 1, with a solid-liquid ratio of 1g:3mL. The mixture was stirred at 500r / min for 7h at 25℃, filtered, washed three times with deionized water, dried at 45℃ for 4h, and heat-treated at 80℃ for 25min to obtain silanized composite fiber.
[0053] The specific preparation method of acidified polypropylene fiber is as follows: the polypropylene fiber is immersed in dilute sulfuric acid with a mass fraction of 7% at a solid-liquid ratio of 1g:6mL, stirred at 300r / min for 60min at 70℃, filtered, washed three times with deionized water, and dried at 45℃ to constant weight for later use.
[0054] Preparation Examples 8-9: Silanized Ammonium Polyphosphate Preparation Example 8 The preparation method of silanized ammonium polyphosphate in this example includes the following steps: The pre-hydrolyzed solution of the silane coupling agent in Preparation Example 2 was added to the reactor, and ammonium polyphosphate was added. The solid-liquid ratio was 1g:3mL. The mixture was stirred at 400r / min for 3h at 30℃. After filtration, the mixture was washed three times with deionized water, dried at 45℃ for 4h, heat-treated at 80℃ for 25min, and pulverized to obtain silanized ammonium polyphosphate.
[0055] Preparation Example 9 The preparation method of silanized ammonium polyphosphate in this example includes the following steps: The pre-hydrolyzed solution of the silane coupling agent in Preparation Example 2 was added to the reactor, and ammonium polyphosphate was added. The solid-liquid ratio was 1g:3mL. The mixture was stirred at 400r / min for 3h at 25℃. After filtration, the mixture was washed three times with deionized water, dried at 45℃ for 4h, heat-treated at 80℃ for 25min, and pulverized to obtain silanized ammonium polyphosphate.
[0056] Example 1 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this embodiment includes the following steps: S1: Take 133.3g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 14.4g of silanized ammonium polyphosphate, 4.8g of pentaerythritol, and 4.8g of dicyandiamide from Preparation Example 8. Stir and disperse at 600r / min for 15min. Add 84g of silanized composite fiber from Preparation Example 6 and stir and impregnate at 300r / min for 20min to obtain mixture A. S2: Take 133.3g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 72g of aluminum hydroxide and 36g of zinc borate, and stir and disperse at 800r / min for 20min to obtain mixture B. S3: Add 900g of P·O 42.5 silicate cement, 300g of slag powder, 12g of nano silica, and 24g of hydroxypropyl methylcellulose to a mixer and dry mix for 3 minutes. Add 230g of deionized water and 96g of ethylene-vinyl acetate emulsion with a solid content of 50%. Stir at 500r / min for 5 minutes to form a uniform slurry. Add mixture A, mixture B, and 168g of vitrified microspheres. Stir at 300r / min for 4 minutes until the system is uniform. Pour the mixture into a mold and place it on a vibrating table to remove air for 2 minutes. Pre-cure at 25℃ and 60% relative humidity for 24 hours. After demolding, transfer it to a standard curing room for 28 days to obtain a substrate with a thickness of about 100mm. S4: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0057] The standard curing temperature is 20±2℃, and the relative humidity is 95%. The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly at a volume ratio of 3:97. The pH of the system was adjusted to 5.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0058] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0059] Example 2 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this embodiment includes the following steps: S1: Take 160g of the polycarboxylated acrylate emulsion from Preparation Example 4 and add it to a mixing container. Add 21.6g of silanized ammonium polyphosphate, 7.2g of pentaerythritol, and 7.2g of dicyandiamide from Preparation Example 9. Stir and disperse at 600r / min for 15min. Add 108g of silanized composite fiber from Preparation Example 7 and stir and impregnate at 300r / min for 20min to obtain mixture A. S2: Take 160g of the polycarboxylated acrylate emulsion from Preparation Example 4 and add it to a mixing container. Add 80g of aluminum hydroxide and 40g of zinc borate. Stir and disperse at 800r / min for 20min to obtain mixture B. S3: Add 900g of P·O 42.5 silicate cement, 300g of silica fume, 12g of nano silica, and 24g of hydroxypropyl methylcellulose to a mixer and dry mix for 3 minutes. Add 200g of deionized water and 96g of ethylene-vinyl acetate emulsion with a solid content of 50%. Stir at 500r / min for 5 minutes to form a uniform slurry. Add mixture A, mixture B, and 168g of ceramsite. Stir at 300r / min for 4 minutes until the system is uniform. Pour the mixture into a mold and place it on a vibrating table to remove air for 2 minutes. Pre-cure at 25℃ and 60% relative humidity for 24 hours. After demolding, transfer it to a standard curing room for 28 days to obtain a substrate with a thickness of approximately 100mm. S4: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0060] The standard curing temperature is 20±2℃ and the relative humidity is 95%.
[0061] The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly at a volume ratio of 3:97. The pH of the system was adjusted to 5.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0062] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0063] Example 3 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this embodiment includes the following steps: S1: Take 133.3g of the polycarboxylated acrylate emulsion from Preparation Example 5 and add it to a mixing container. Add 14.4g of silanized ammonium polyphosphate, 4.8g of pentaerythritol, and 4.8g of dicyandiamide from Preparation Example 8. Stir and disperse at 600r / min for 15min. Add 84g of silanized composite fiber from Preparation Example 6 and stir and impregnate at 300r / min for 20min to obtain mixture A. S2: Take 133.3g of the polycarboxylated acrylate emulsion from Preparation Example 5 and add it to a mixing container. Add 72g of aluminum hydroxide and 36g of zinc borate, and stir and disperse at 800r / min for 20min to obtain mixture B. S3: Add 900g of P·O 42.5 silicate cement, 300g of fly ash, 12g of nano silica, 24g of hydroxypropyl methylcellulose and 60g of pretreated phosphogypsum to a mixer and dry mix for 3 minutes. Add 230g of deionized water and 96g of ethylene-vinyl acetate emulsion with a solid content of 50% and stir at 500r / min for 5 minutes to form a uniform slurry. Add mixture A, mixture B and 168g of expanded perlite and stir at 300r / min for 4 minutes until the system is uniform. Pour the mixture into a mold and place it on a vibrating table to remove air for 2 minutes. Pre-cure it at 25℃ and 60% relative humidity for 24 hours. After demolding, transfer it to a standard curing room for 28 days to obtain a substrate with a thickness of about 100mm. S4: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0064] The standard curing temperature is 20±2℃ and the relative humidity is 95%.
[0065] The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly at a volume ratio of 3:97. The pH of the system was adjusted to 5.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0066] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0067] The preparation method of pretreated phosphogypsum includes the following steps: The raw phosphogypsum ore was mixed with lime at a mass ratio of 100:3, ball-milled for 45 minutes, aged at 60°C for 24 hours, dried at 45°C for 3 hours, ground, and passed through a 200-mesh standard sieve. The sieve-underfill material was collected to obtain pretreated phosphogypsum.
[0068] Example 4 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this embodiment includes the following steps: S1: Take 80g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 7.2g of silanized ammonium polyphosphate, 2.4g of pentaerythritol, and 2.4g of dicyandiamide from Preparation Example 8. Stir and disperse at 600r / min for 15min. Add 48g of silanized composite fiber from Preparation Example 6 and stir and impregnate at 300r / min for 20min to obtain mixture A. S2: Take 80g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 48g of aluminum hydroxide and 24g of zinc borate. Stir and disperse at 800r / min for 20min to obtain mixture B. S3: Add 840g of P·O 42.5 silicate cement, 240g of fly ash, 6g of nano silica, 12g of hydroxypropyl methylcellulose and 60g of pretreated phosphogypsum to a mixer and dry mix for 3 minutes. Add 256g of deionized water and 72g of ethylene-vinyl acetate emulsion with a solid content of 50% and stir at 500r / min for 5 minutes to form a uniform slurry. Add mixture A, mixture B and 120g of expanded perlite and stir at 300r / min for 4 minutes until the system is uniform. Pour into a mold and place on a vibrating table to degas for 2 minutes. Pre-cure at 25℃ and 60% relative humidity for 24 hours. After demolding, transfer to a standard curing room for 28 days to obtain a substrate with a thickness of about 100mm. S4: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0069] The standard curing temperature is 20±2℃ and the relative humidity is 95%.
[0070] The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly in a volume ratio of 5:95. The pH of the system was adjusted to 4.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 30 min at 30 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0071] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0072] The preparation method of pretreated phosphogypsum includes the following steps: The raw phosphogypsum ore was mixed with lime at a mass ratio of 100:3, ball-milled for 45 minutes, aged at 60°C for 24 hours, dried at 45°C for 3 hours, ground, and passed through a 200-mesh standard sieve. The sieve-underfill material was collected to obtain pretreated phosphogypsum.
[0073] Example 5 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this embodiment includes the following steps: S1: Take 200g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 21.6g of silanized ammonium polyphosphate, 7.2g of pentaerythritol, and 7.2g of dicyandiamide from Preparation Example 8. Stir and disperse at 600r / min for 15min. Add 120g of silanized composite fiber from Preparation Example 6 and stir and impregnate at 300r / min for 20min to obtain mixture A. S2: Take 200g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 96g of aluminum hydroxide and 48g of zinc borate. Stir and disperse at 800r / min for 20min to obtain mixture B. S3: Add 960g of P·O 42.5 silicate cement, 360g of silica fume, 24g of nano silica, 36g of hydroxypropyl methylcellulose and 60g of pretreated phosphogypsum to a mixer and dry mix for 3 minutes. Add 190g of deionized water and 120g of ethylene-vinyl acetate emulsion with a solid content of 50%. Stir at 500r / min for 5 minutes to form a uniform slurry. Add mixture A, mixture B and 216g of lightweight ceramsite. Stir at 300r / min for 4 minutes until the system is uniform. Pour into a mold and place on a vibrating table to degas for 2 minutes. Pre-cure at 25℃ and 60% relative humidity for 24 hours. After demolding, transfer to a standard curing room for 28 days to obtain a substrate with a thickness of about 100mm. S4: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0074] The standard curing temperature is 20±2℃ and the relative humidity is 95%.
[0075] The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly in a volume ratio of 5:95. The pH of the system was adjusted to 4.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 30 min at 30 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0076] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0077] The preparation method of pretreated phosphogypsum includes the following steps: The raw phosphogypsum ore was mixed with lime at a mass ratio of 100:3, ball-milled for 45 minutes, aged at 60°C for 24 hours, dried at 45°C for 3 hours, ground, and passed through a 200-mesh standard sieve. The sieve-underfill material was collected to obtain pretreated phosphogypsum.
[0078] Example 6 The difference between this embodiment and embodiment 5 is as follows: The amount of pretreated phosphogypsum used is 120g.
[0079] Everything else is the same as in Example 5.
[0080] The preparation method of pretreated phosphogypsum includes the following steps: The raw phosphogypsum ore was mixed with lime at a mass ratio of 100:5, ball-milled for 60 minutes, aged at 60°C for 24 hours, dried at 45°C for 3 hours, ground, and passed through a 200-mesh standard sieve. The material passing through the sieve was collected to obtain pretreated phosphogypsum.
[0081] Comparative Example 1 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this comparative example includes the following steps: S1: 900g of P·O 42.5 silicate cement, 300g of slag powder, 12g of nano-silica, and 24g of hydroxypropyl methylcellulose were added to a mixer and dry-mixed for 5 minutes. Then, 230g of deionized water, 96g of ethylene-vinyl acetate emulsion with a solid content of 50%, and 266.6g of the polycarboxylated acrylate emulsion from Preparation Example 3 were added. The mixture was stirred at 500 rpm for 5 minutes to form a homogeneous slurry. Finally, 14.4g of silanized ammonium polyphosphate, 4.8g of pentaerythritol, and bis(hydroxypropyl)methylcellulose from Preparation Example 8 were added. 4.8g of cyanamide, 72g of aluminum hydroxide, 36g of zinc borate and 84g of silanized composite fiber from Preparation Example 6 were stirred at 300r / min for 3min until the system was homogeneous. 168g of vitrified microspheres were added and stirred at 300r / min for 4min until the system was homogeneous. After being poured into a mold, the mixture was placed on a vibration table to remove air for 2min. It was then allowed to stand for 24h at a temperature of 25℃ and a relative humidity of 60%. After demolding, it was transferred to a standard curing room for 28d to obtain a substrate with a thickness of about 100mm. S2: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0082] The standard curing temperature is 20±2℃ and the relative humidity is 95%.
[0083] The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly at a volume ratio of 3:97. The pH of the system was adjusted to 5.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0084] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0085] Comparative Example 2 S1: P·O 900g of 42.5 silicate cement, 300g of slag powder, 12g of nano silica, and 24g of hydroxypropyl methylcellulose were added to a mixer and dry-mixed for 5 minutes. Then, 376g of deionized water and 96g of ethylene-vinyl acetate emulsion with a solid content of 50% were added and stirred at 500r / min for 5 minutes to form a uniform slurry. Then, 14.4g of silanized ammonium polyphosphate, 4.8g of pentaerythritol, 4.8g of dicyandiamide, 72g of aluminum hydroxide, 36g of zinc borate, and 84g of silanized composite fiber from Preparation Example 8 were added and stirred at 300r / min for 3 minutes until the system was uniform. Then, 168g of vitrified microspheres were added and stirred at 300r / min for 4 minutes until the system was uniform. After pouring into a mold, the mixture was placed on a vibrating table for 2 minutes to remove air and was pre-cured at 25℃ and 60% relative humidity for 24 hours. After demolding, the mixture was transferred to a standard curing room for 28 days to obtain a substrate with a thickness of about 100mm. S2: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0086] The standard curing temperature is 20±2℃ and the relative humidity is 95%.
[0087] The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly at a volume ratio of 3:97. The pH of the system was adjusted to 5.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0088] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0089] Comparative Example 3 The preparation method of the lightweight flame-retardant cement-based composite wall panel in this comparative example includes the following steps: S1: Take 133.3g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 84g of the silanized composite fiber from Preparation Example 6 and stir and impregnate at 300r / min for 20min to obtain mixture A. S2: Take 133.3g of the polycarboxylated acrylate emulsion from Preparation Example 3 and add it to a mixing container. Add 72g of aluminum hydroxide and 36g of zinc borate, and stir and disperse at 800r / min for 20min to obtain mixture B. S3: 900g of P·O 42.5 silicate cement, 300g of slag powder, 12g of nano silica, and 24g of hydroxypropyl methylcellulose were added to a mixer and dry-mixed for 3 minutes. 230g of deionized water and 96g of ethylene-vinyl acetate emulsion with a solid content of 50% were added and stirred at 500r / min for 5 minutes to form a uniform slurry. 14.4g of silanized ammonium polyphosphate, 4.8g of pentaerythritol, and 4.8g of dicyandiamide from Preparation Example 8 were added and stirred at 300r / min for 3 minutes until the system was uniform. Mixture A, mixture B, and 168g of vitrified microspheres were added and stirred at 300r / min for 4 minutes until the system was uniform. After pouring into a mold, the mixture was placed on a vibrating table for 2 minutes to remove air. It was then allowed to stand for 24 hours at a temperature of 25℃ and a relative humidity of 60%. After demolding, it was transferred to a standard curing room for 28 days to obtain a substrate with a thickness of approximately 100mm. S4: Sand the substrate surface smooth and remove dust, then evenly coat it with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution at a coating weight of 80g / m². 2 After being left at room temperature for 45 minutes, a water-based UV-curable coating is applied by roller. After curing by a UV curing machine, the coating is cut and trimmed to obtain a lightweight flame-retardant cement-based composite wall panel.
[0090] The standard curing temperature is 20±2℃, and the relative humidity is 95%. The preparation method of the prehydrolyzed solution of methacryloyloxypropyltrimethoxysilane includes the following steps: Methacryloxypropyltrimethoxysilane and an aqueous ethanol solution were mixed evenly at a volume ratio of 3:97. The pH of the system was adjusted to 5.0 using a 10% acetic acid solution. The mixture was stirred at 300 r / min for 60 min at 25 °C to obtain a pre-hydrolyzed solution of methacryloxypropyltrimethoxysilane.
[0091] The ethanol-water solution is prepared by mixing anhydrous ethanol and deionized water in a volume ratio of 9:1.
[0092] Performance testing The lightweight flame-retardant cement-based composite wall panels prepared in Examples 1-6 and Comparative Examples 1-3 were subjected to the following performance tests; the reference standards were GB 8624-2012, GB / T 9978.8-2008 and GB / T 50081-2019, and the specific test data are shown in Table 1.
[0093] Table 1. Performance test data of lightweight flame-retardant cement-based composite wall panels prepared in Examples 1-6 and Comparative Examples 1-3
[0094] The dry densities of Examples 1-6 all meet the requirements for lightweight wall panels, with a density grade ≤1300 kg / m³. 3 Examples 2, 5, and 6, which use ceramsite, have slightly higher densities, while Examples 1, 3, and 4, which use vitrified microspheres and expanded perlite, have relatively lower densities.
[0095] In terms of mechanical properties, Example 6 exhibits superior compressive strength. This is attributed to the combination of highly reactive silica fume and a high dosage of pretreated phosphogypsum. The ultrafine silica fume powder fills the micropores and exerts high pozzolanic activity, while the pretreated phosphogypsum eliminates interference from acidic impurities and can activate the secondary hydration of auxiliary cementitious materials through sulfate ions, effectively improving the density and mechanical stability of the substrate. The compressive strength of Example 5 is slightly lower than that of Example 6. Appropriately increasing the phosphogypsum dosage can further optimize the matrix structure and improve strength. Example 4 has relatively lower compressive strength due to lower total cementitious material and emulsion dosages compared to other examples, but it still meets the requirements for lightweight wall panels.
[0096] Comparative Example 1 has the same formulation as Example 1, but uses a one-step mixing process. The compressive strength and fire resistance limit decreased slightly, indicating that the stepwise premixing and coating process can effectively optimize the interface structure and improve the uniformity and overall stability of the matrix.
[0097] Regarding combustion performance, this application constructs a multi-temperature-zone synergistic flame-retardant system using intumescent flame retardant A and inorganic flame retardant B, combined with in-situ fixation of the flame-retardant components using polycarboxylated acrylate. Examples 1-6 all achieved A2 rating. Comparative Example 2 completely eliminated the polycarboxylated acrylate interface-modified emulsion, resulting in uneven dispersion of the flame-retardant components, making it difficult to form a continuous and dense char layer at high temperatures, leading to a decrease in both mechanical properties and fire resistance limit. In Comparative Example 3, flame retardant A was not pre-coated, resulting in decreased compressive strength and flame-retardant performance.
[0098] In addition, the UV-cured coating on the surface of the board mainly serves to decorate and improve the surface's waterproof, stain-resistant, and wear-resistant effects; the core indicators of the wall panel, such as compressive strength and fire resistance limit, are determined by the substrate itself, and the UV coating will not significantly change the mechanical and fire-resistant properties of the substrate.
Claims
1. A lightweight, flame-retardant cement-based composite wall panel, characterized in that, The substrate includes a substrate and a UV-curable coating laminated on the surface of the substrate, wherein the substrate is made of the following raw materials in parts by weight: The ingredients are: 70-80 parts cement, 20-30 parts auxiliary cementitious materials, 4-10 parts silanized composite fiber, 1-3 parts flame retardant A, 6-12 parts flame retardant B, 6-15 parts polycarboxylated acrylate, 10-18 parts lightweight porous aggregate, 3-5 parts water-based environmentally friendly adhesive, 0.5-2 parts nano silica, 1-3 parts hydroxypropyl methylcellulose, and 32-39 parts water.
2. The lightweight flame-retardant cement-based composite wall panel according to claim 1, characterized in that, The auxiliary cementing material is selected from any one of slag powder, fly ash, and silica fume.
3. The lightweight flame-retardant cement-based composite wall panel according to claim 1, characterized in that, The lightweight porous aggregate is selected from any one of expanded perlite, vitrified microspheres, and ceramsite.
4. The lightweight flame-retardant cement-based composite wall panel according to claim 1, characterized in that, The flame retardant A comprises silanized ammonium polyphosphate, pentaerythritol, and dicyandiamide.
5. The lightweight flame-retardant cement-based composite wall panel according to claim 4, characterized in that, The flame retardant B comprises aluminum hydroxide and zinc borate.
6. The lightweight flame-retardant cement-based composite wall panel according to claim 1, characterized in that, The polycarboxylated acrylate is added in the form of a polycarboxylated acrylate emulsion, and its preparation method includes the following steps: Under an inert atmosphere, 42-48 parts of butyl acrylate, 2-5 parts of acrylic acid, 1-3 parts of methacrylic acid, 0.5-2 parts of itaconic acid, 1-3 parts of N-hydroxymethylacrylamide, and 12-20 parts of polyethylene glycol methyl ether methacrylate are mixed evenly and added to an aqueous phase containing emulsifier. After pre-emulsification, the temperature is raised to 70-80℃, an initiator is added, and the reaction is carried out for 4-6 hours. After neutralization, an acrylate emulsion is obtained.
7. The lightweight flame-retardant cement-based composite wall panel according to claim 6, characterized in that, The method for preparing the silanized composite fiber includes the following steps: After mixing alkali-free glass fiber and acidified polypropylene fiber, the mixture is impregnated in a pre-hydrolyzed solution of silane coupling agent, mixed at 25~30℃ for 5~7h, followed by solid-liquid separation, washing, drying, and heat treatment to obtain silanized composite fiber.
8. The lightweight flame-retardant cement-based composite wall panel according to claim 7, characterized in that, The method for preparing the pre-hydrolyzed solution of the silane coupling agent includes the following steps: Mix the silane coupling agent and the ethanol aqueous solution evenly, adjust the pH to 3.5~5.5, and mix for 40~60 minutes to obtain the pre-hydrolyzed solution.
9. The lightweight flame-retardant cement-based composite wall panel according to claim 1, characterized in that, The substrate also includes 5 to 10 parts by weight of pretreated phosphogypsum.
10. A method for preparing a lightweight flame-retardant cement-based composite wall panel as described in any one of claims 1 to 9, characterized in that, Includes the following steps: S1: Mix a portion of polycarboxylated acrylate and flame retardant A evenly, add silanized composite fiber and mix evenly to obtain mixture A; S2: Mix the remaining polycarboxylated acrylate and flame retardant B evenly to obtain mixture B; S3: Mix cement, auxiliary cementitious materials, nano silica, hydroxypropyl methylcellulose, and optional pretreated phosphogypsum evenly, add water and water-based environmentally friendly adhesive and mix evenly, add mixture A, mixture B and lightweight porous aggregate and mix evenly, pour into mold, vent, allow to stand for pre-curing, demold, and after standard curing, obtain the substrate; S4: After coating the substrate surface with methacryloyloxypropyltrimethoxysilane pre-hydrolyzed solution, the coating is rolled, cured, and post-treated to obtain a lightweight flame-retardant cement-based composite wall panel.
Citation Information
Patent Citations
Light composite wallboard and preparation method thereof
CN104692722A